Kneeler - Ghosh, Ayan (2023)
Kneeler at the St. Thomas Church altar. A kneeler is a cushion (a tuffet or hassock) used for resting the knees in a kneeling position during Christian prayer. Seen in the background are the brass eagle lectern and the grand piano.